“We’re in compliance”: Reconciling teachers’ work as resistance to neoliberal policies - Duarte, Bryan J.; Brewer, Curtis A. (Education Policy Analysis Archives, 2022)
Neoliberal polices such as standardized testing, teacher evaluation, and student performance accountability serve as market pressures that dictate teachers’ work. In this paper, we employ critical policy analysis (CPA) and critical ethnography in order to bridge theory and method. Specifically, we apply de Certeau’s (1984) theory of consumption to examine the clandestine ways that teachers creatively resist the policies that constrain them. Our findings, which are presented in three vignettes, demonstrate the ways in which teachers tactically read policy and engage in passive compliance. We conclude by discussing how the qualities of our participants’ subtle acts of resistance blur the line between compliance and resistance, which has implications for the study of resistance to neoliberal policies.